2010
DOI: 10.1007/s11738-010-0547-1
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat pre-treatment increases activities of antioxidant enzymes and reduces lipid peroxidation in salt-stressed cucumber leaves

Abstract: To investigate whether paraquat (PQ) is involved in regulation of antioxidant enzymes and lipid peroxidation under short-term salt stress, and to elucidate the physiological mechanism of salt stress mitigated by PQ, a cucumber cultivar (cv. Chunguang no. 2) was exposed to 100 mM NaCl for 48 h after pre-treatment with 10 lM PQ for 1 h. When compared to the control, salt stress increased the levels of malonaldehyde (MDA), superoxide radical (O 2 Á-) and hydrogen peroxide (H 2 O 2 ) and the activities of antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
(73 reference statements)
3
8
0
Order By: Relevance
“…4G) which suggests that CAT appears not to be an effective scavenger of H 2 O 2 in Vigna radiata, and the increase in H 2 O 2 is possibly due to the decreased activity of CAT (Parida and Jha, 2010). A decline in CAT activity due to salt stress was also reported in different crop species (Sekmen et al, 2007;Aghaei et al, 2009;Lin et al, 2010) which agrees with our results. Importantly, proline-or betaine-pretreated salt-stressed seedlings maintained a higher CAT activity as compared to the seedlings subjected to salt stress without pre-treatment.…”
Section: Fig 6 Changes In H 2 O 2 Concentration (A) and Lipid Peroxisupporting
confidence: 91%
“…4G) which suggests that CAT appears not to be an effective scavenger of H 2 O 2 in Vigna radiata, and the increase in H 2 O 2 is possibly due to the decreased activity of CAT (Parida and Jha, 2010). A decline in CAT activity due to salt stress was also reported in different crop species (Sekmen et al, 2007;Aghaei et al, 2009;Lin et al, 2010) which agrees with our results. Importantly, proline-or betaine-pretreated salt-stressed seedlings maintained a higher CAT activity as compared to the seedlings subjected to salt stress without pre-treatment.…”
Section: Fig 6 Changes In H 2 O 2 Concentration (A) and Lipid Peroxisupporting
confidence: 91%
“…In the present study, MDA levels increased significantly during salt stress compared to controls, while the Si reduced MDA levels and adjusted the destructive effects of salinity on membrane lipids of borage. Also, the results of research on rice (Tijen and Ismail 2005), cotton (Gossypium herbaceum L.) (Diego et al 2003) and cucumber (Lin et al 2011) showed that MDA levels increased under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have announced that salt tolerance was enhanced in transgenic plants (Begcy et al 2011;Hao et al 2011;Jacobs et al 2011;Rahnama et al 2011;Wei et al 2011), the results are obtained under abnormal growth condition and not tested in the field. Stress resistance training and exogenous application of growth and osmotic regulators have been demonstrated to ameliorate plant salt stress (Amzallag et al 1990;Umezawa et al 2000;Chattopadhayay et al 2002;Demiral and Turkan 2006;Chen et al 2007;Kaya et al 2007;Wahid et al 2007;Athar et al 2008;Zheng et al 2008;Reezi et al 2009;Chang et al 2010;Cimrin et al 2010;Khan et al 2010;Akram and Ashraf 2011;Fan et al 2011;Idrees et al 2011;Lin et al 2011;Nazar et al 2011;Sakr et al 2012). These methods are derived from plant eco-physiology theories and are generalized in Table 1.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%